Kajian Teknis Optimasi Produksi Alat Gali Muat dan Alat Angkut Pada Kegiatan Pengupasan Overburden Berdasarkan Efisiensi Biaya Operasional Di Pit Barat PT. Allied Indo Coal Jaya Kota Sawahlunto - Dita Aprilia Istiqamah; Mulya Gusman (Journals Mining Engineering : Bina Tambang, 2020)
Abstract. In an open pit, in overburden removal and hauling overburden activities in the western pit of PT. Allied Indo Coal Jaya operates 1 unit of CAT 330D2 L back hoe excavator as a digger and 3 units dump truck HINO 500 FM 260 JD. The problem currently is not achieving the overburden production target in the western pit in July 2019 which is 54,000 bcm while the actual production is 50,966.19 bcm. The method used in this study is the match factor method. The existence of the incompatibility of work between the loading and hauling equipment and conveyance, it is necessary to optimize the productivity of the equipment and the compatibility of work between the loading and unloading equipment. The actual match factor of the loading and hauling equipment is 0.75. To achieve match factor, carried out an optimization of the hauling cycle time and increase the number of bucket excavator filling so the match factor reaches 0.99. Then the total production of loading was 54,552.38 bcm/month and hauling equipment was 54,252.14 bcm/month. From the calculation results obtained the magnitude of the operational costs of the loading and hauling equipment for overburden removal before being analyzed Rp. 193,317,429 or Rp. 3,963 / bcm. After being analyzed for peeling overburden in accordance with the planned production target, a cost of Rp. 204,846,453 or Rp. 3,755 / bcm.Keyword: production, overburden, match factor, cycle time, operational cost